Analisis Pengeluaran dan Pola Konsumsi Pangan Rumah Tangga Petani Cengkeh di Kecamatan Lasusua - Aemana, Ummu; Limi, Muhammad Aswar; Zani, Munirwan; Mariani, Mariani (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2019)
This study aims to determine Total food and non-food expenditure on clove farmer households in Totallang Village, Lasusua District, North Kolaka Regency; Household Food Consumption Pattern of Clove Farmers in Totallang Village, Lasusua District, NorthKolaka Regency. This research was conducted in Totallang Village, Lasusua District, NorthKolaka Regency with a total sample of 65 respondents. Data collection techniques in this study were interview techniques by conducting a question and answer directly with the respondents of the study used as primary data collection techniques. The library technique was used as a secondary data collection technique. Secondary data was obtained from Totallang Village Office, North Kolaka Regency Central Bureau of Statistics, and Southeast Sulawesi Provincial Statistics Agency. The data analysis used in this study was the analysis of household expenditure allocation and descriptive analysis. The results showed that community food consumption was very high compared to non-food consumption, this was influenced by basic needs that continue to increase every time and people tend to prioritize primary needs rather than secondary needs to be able to continue to survive and income affect the consumption patterns of respondents because of the variety of menus consumed by the people in the research villages showed a different consumption pattern.